(untitled) (SCIÉNDO INGENIUM, 2024)
This research work presents the proposal of an artificial intelligence model with human brain-computer interaction for virtual communication. Characteristics, advantages and disadvantages of application are determined. It is concluded that it is possible to develop a Brain-Computer Interface prototype to achieve virtual communication in people unable to communicate. For this, apart from the 3 phases: registration of brain signals, extraction of characteristics and translation into actions; a feedback from the user is included; and as a methodology, a match of activities was used.